Benefícios do aleitamento materno exclusivo durante os primeiros meses de vida do recém-nascido - Ian Xavier Paschoeto dos Santos; Aline de Freitas Fleury Curado; Anna Raquel Ribeiro Sa Freire; Beatriz Arruda de Oliveira Martins; Rebeca Magalhães Barros; Maria Augusta de Macedo Wehbe (Sociedade Brasileira de Pediatria, 2022)
To have breastfeeding only until the ideal age is still an important challenge in Brazil. There are several factors that play a role in interrupting exclusive breastfeeding, from false information to difficulties in offering breast milk. However, it is up to healthcare professionals to have full mastery of aspects related to the benefits of breast milk for the health and well-being of infants and nursing mothers for better care in their follow-up. As a result, we undertook a narrative literature review, with emphasis on the main aspects and benefits of breast milk for infant health, based on 17 papers found in the Medline and SciELO databases. We selected studies that dealt with the purpose of the review, based on assessing the respective abstracts. From the review of selected studies, we found that Exclusive Breastfeeding has benefits beyond the nutritional field and offers a lower risk of developing chronic diseases such as diabetes, hypertension, obesity; and provides protection against different types of cancer to the mother. There was also a discussion that Primary Healthcare plays a key role in ensuring that infants receive breast milk for the proper amount of time. On the other hand, there are still obstacles in the promotion of quality breastfeeding, especially for mothers and infants in situations of greater social vulnerability, an aspect that must be considered in healthcare.